2021
DOI: 10.3389/fnagi.2021.734866
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Activities and Their Relationship With MRI Measures of Brain Structure, Functional Connectivity, and Cognition in the UK Biobank Cohort

Abstract: Introduction: This study aimed to evaluate whether engagement in leisure activities is linked to measures of brain structure, functional connectivity, and cognition in early old age.Methods: We examined data collected from 7,152 participants of the United Kingdom Biobank (UK Biobank) study. Weekly participation in six leisure activities was assessed twice and a cognitive battery and 3T MRI brain scan were administered at the second visit. Based on responses collected at two time points, individuals were split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…SB is also associated with cognitive and structural brain aging ( 7 , 11 , 12 , 24 26 ), although associations with cognition, and modification of these associations by PA, lack clarity in the literature ( 27 , 28 ). Distinctive SB domains may have different effects on cognition, with cognitively passive SBs like watching TV demonstrating negative associations with cognition and cognitively active SBs like computer use or reading showing positive associations with cognition ( 7 , 24 , 29 31 ). In addition, previous work has linked SBs with dementia and Alzheimer’s disease in case-control studies ( 11 ).…”
mentioning
confidence: 99%
“…SB is also associated with cognitive and structural brain aging ( 7 , 11 , 12 , 24 26 ), although associations with cognition, and modification of these associations by PA, lack clarity in the literature ( 27 , 28 ). Distinctive SB domains may have different effects on cognition, with cognitively passive SBs like watching TV demonstrating negative associations with cognition and cognitively active SBs like computer use or reading showing positive associations with cognition ( 7 , 24 , 29 31 ). In addition, previous work has linked SBs with dementia and Alzheimer’s disease in case-control studies ( 11 ).…”
mentioning
confidence: 99%
“…For example, increased functional connectivity of the somato/motor network may also reflect increased physical activity or social connectedness and stimulation 85 in parents with more children (higher parity), as well as additional support provided to parents by their children in later years 86,87 . Increased physical, leisure, and social activity are known to increase functional connectivity in both somato/motor and hippocampal regions, providing a potential mechanism for the present results 88,89 . Furthermore, the increased novelty, complexity, and cognitive challenge inherent in the caregiving environment may provide a form of environmental enrichment for parents, which when sustained across the lifespan, might be beneficial for neural and cognitive resilience in later life 1,34,35,90,91 .…”
Section: Discussionmentioning
confidence: 58%
“…Similar results were found by Fleck et al (2019), who reported that the exercise factor group displayed no effect on cognition. The absence of associations between leisure and physical activities and cognition may be due to the lack of standardization of these variables, such as the frequency, intensity, duration, and type of activities, as concluded by some authors in previous studies (Wang et al, 2012;Anatürk et al, 2021).…”
Section: Discussionmentioning
confidence: 96%